Dr. Eckart Knoche — Deep Plane Facelift - Knoche, Eckart (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Eckart Knoche, Germany. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003149; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; germany